‘I Was the First Westerner, the Only English Person’: Discursive Construction of National Identity - T V Dubrovskaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2015)
This study focuses on the issue of discursive construction of national identity. It aims to reveal how pragma-linguistic tools are exploited to construct and re-construct national identity, as well as to define how flexible it can be and how identities of the speakers correlate in dialogue. The research can be viewed as a case-study; the data for analysis come from three issues of the English language talk-show ‘Insight Germany’ on the German TV channel Deutsche Welle. Certain claims from social theories of identity are taken as a point of reference. In terms of methodology, the study draws on pragma-linguistic analysis, which takes into consideration both linguistic features of the text and extra-linguistic factors, such as personalities and their social characteristics as well as pragmatic purposes. As a result, the authors identify three levels of discursive construction of national identity: meaningful, communicative and meta-linguistic. The meaningful and meta-linguistic levels are described through the listing of tactics. The communicative level embraces heterogeneous phenomena and demands further explorations. The range of linguistic resources used to construct national identity is not limited and includes nominative units for nations and ethnicities, geographical names, names of languages, evaluative adjectives with negative and positive connotations, phonetic variants of words, and lexical and syntactic expressions of modality. The presenter’s role in interactive construction of national identity is also defined.